Be in Your Element: The Joint Effect of Human Resource Management Strength and Proactive Personality on Employee Creativity - Zhang, Jiexuan; Zhu, Fei; Liu, Ning; Cai, Zijun (Frontiers in Psychology, 2022)
Employee creativity is fast becoming a part and parcel in the wake of the increasing volatility of the employment market and the complexity of job demands. Drawing from the actor-context interactionist theoretical approach and career construction theory, this paper adds to current research by exploring the serial mediating effect of job crafting (JC) and career adaptability (CA) in the impact of human resource management strength (HRMS) on employee creativity. Furthermore, we suggest that proactive personality interacts with HRMS to jointly influence creativity. Survey data from samples of 297 (Study 1) and 390 (Study 2) employees largely confirm our model. Our findings show that HRMS positively impacts employee creativity via serial mediation of job crafting and career adaptability, and proactive personality negatively moderates the process. The paper confirms and expands the interactionist theoretical perspective of creativity, highlights the significance of integration of contextual factors, individual characteristics, and career construction, and makes certain practical sense.